THE ROLE OF THE UN IN THE PRESERVATION AND DEVELOPMENT OF NATIONAL LANGUAGES IN THE CONTEXT OF GLOBALIZATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article is devoted to the analysis of the role of the United Nations (UN) in the preservation and development of national languages in the context of globalization. The article examines the UN initiatives aimed at supporting linguistic diversity, as well as the role of international organizations in promoting languages within the framework of global communications. Special attention is paid to the UN strategies and programs aimed at preventing the disappearance of rare and endangered languages. documents, such as the Declaration on the Rights of Indigenous Peoples and International Mother Language Day, and assesses their impact on the preservation of languages in the face of the growing influence of global languages. The article also examines the challenges faced by national languages in the era of digital technologies and media platforms.